Наблюдения върху характеристиките, хронологията и обема на раннобронзови аскоси от Юнаците и Огняново, Пазарджишко - Petar Minkov (Българско е-Списание за Археология)
The present research concerns 26 complete and restored askoi found during archaeological excavations at the settlement mounds near the modern villages of Yunatsite and Ognyanovo (Maltepe), district of Pazardzhik. The aim of this study is to present some new and additional data on the characteristics, stratigraphic positions and chronology of the vessels. The methodology used includes a detailed catalogue and comparison with the known Early Bronze Age finds from the Bulgarian lands and the neighbouring territories. Although the artifacts of this category of vessels from the mentioned sites have already been considered in the literature, their reassessment gives new data on their characteristics. This allows their comparison with similar vessels from neighbouring territories. An attempt has been made to create an internal typological scheme for the settlement mound of Yunatsite.